SPORT TOURISM - Ridho Bastanta Tarigan; Melky Pangemanan Agustinus; Robin Butarbutar (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Sport tourism is an increasingly popular phenomenon, where individuals travel to participate in or watch sporting events. It represents a significant aspect of the modern tourism industry, merging interests in sports and travel. This article aims to explore the contributions of sport tourism to the local economy and its impacts on society and the environment. The findings indicate that sport tourism not only drives economic growth through increased tourist spending but also enhances social interactions and introduces local culture to visitors. The study emphasizes the need for sustainable practices to maximize benefits while addressing potential challenges.